Can waves be created with Yoga poses? (How to Apply Physics at Home during COVID time) - Liu, Yadi; Sharma, Dipti (European Journal of Applied Sciences, 2021)
It is always good to see how Physics can be applied in real-world applications and in everyday life activities. This experimental work shows the application of Physics in Yoga. Yoga is a group of exercises that are performed physically, mentally, and spiritually which originated in ancient India. Yoga is a good combination of Arts, Sciences, and Philosophy. Today, the entire world is following Yoga as a set of exercises in the form of poses to keep their body healthy, calm, and happy. Have you ever thought that the human body can follow circular motion? Let’s think about it. If you notice and look at your own body parts, you will find that most of the parts of the human body are connected to one end and free to another end, for example, a finger, an arm, a leg, head, hair, etc. Based on the Physical concept of circular motion, any object can move in the circular motion or follow part of the circle if it is connected to one end and free to the other end and given the required radial acceleration to move. This is an honor project conducted as hands on activities at home during COVID time during spring 2021 semester. It reports that how waves can be formed using yoga poses following Physical concepts of circular motion and other linear motion. It also shows how Physics can be applied as hands on activities with Yoga and the concept of Physics were used during COVID time.